Portugal dos Pequenitos as an urban laboratory for rehearsing national identity - Pinto, P. T. (2022)
Portugal dos Pequenitos (literally, ‘Portugal for the Little Ones’), a theme park built in Portugal as part of the Centenarian Commemorations of the Portuguese Nation of 1940, has been considered one of the most controversial pieces of Portuguese architecture in the 20th century. Designed between 1937 and 1962 by Architect Cassiano Branco, at the initiative of Bissaya Barreto, it features reproductions of uniquely typical Portuguese architecture built to a child's scale. It includes buildings from mainland Portugal, from the Azores and Madeira islands and from the colonial territories in Africa and Asia. The main aims of this paper are twofold: firstly, to frame Cassiano Branco's architecture in its specific context, in terms of historical contingencies and architectural controversies during the Estado Novo (New State) Portuguese dictatorship (1933–1974), and secondly, to assess the importance of Portugal dos Pequenitos as a laboratory for rehearsing an idyllic urban environment, applying hypothetical principles of national identity.